Shaping pathways to gambling consumption? An analysis of the promotion of gambling and non-gambling activities from gambling venues - Bestman, A.; Thomas, S.; Randle, M.; Pitt, H.; Daube, Mike; Pettigrew, Simone (Taylor & Francis, 2015)
Background: In Australia, venues which provide gambling activities also provide activities that are utilised by families and children. However, there has been limited theoretical or empirical discussion about whether engagement with non-gambling activities may play a role in shaping pathways to current or future engagement in gambling within these environments. We examined marketing tactics for non-gambling and gambling activities in Clubs. Using this data, we propose a conceptual model to test the role of non-gambling activities within gambling environments in shaping gambling attitudes and consumption intentions. Methods: This study used a mixed method interpretive content analysis to review the marketing activities on the websites of a sample of 65 registered Clubs in New South Wales, Australia. We identified the extent and nature of techniques used to market gambling and non-gambling activities, particularly non-gambling activities directed towards families and children. Results: Clubs use various marketing tactics to appeal to families and encourage parents to bring their children into venues. We hypothesise that marketing aimed at bringing children and families into gambling environments may play a role in shaping children’s and adults perceptions of these environments and may be influential in the development of a pathway that increases the likelihood that children will continue to visit these environments as adults, and subsequently the extent to which they engage in gambling later in life. Conclusions: Future research should explore how the presence of family-friendly activities in Clubs and other venues with gambling activities may play a role in shaping future gambling attitudes and behaviours.